Association of sperm protamine1 and protamine2 transcript content with paternal age: A cross-sectional study - Baharan Dolatshahi; Mehran Dorostghoal; Hamid Galehdari; Masoud Hemadi (International Journal of Reproductive BioMedicine)
Background: Over the last decade, there has been a significant increase in average paternal age.